Eco-friendly management of mealybug and wilt in pineapple (The Journal of Plant Protection Sciences, 2020)
In an on-farm RBD trial (3 treatments, 8 replicates) in 2006-07 at Chopra, Islampur, Uttar Dinajpur, West Bengal, for eco-friendly pest management of mealy bug, Dysmicoccus brevipes Cockerell in  pineapple, the treatments were: T1 [Farmers’ practice: phorate 10 G @ 20 kgha-1 during planting + monocrotophos 36% EC @ 0.03% at 100 DAP + endosulfan 35% EC @ 0.02% during 150-180  DAP]; T2 [Treating planting materials (basal portion) with monocrotophos 36% EC @ 0.02% + phorate 10 G @ 15 kg ha-1at 100 DAP + Neem oil 1500 ppm spray @ 2.5 m/L-1 at 150 DAP]; T3 [Treating planting materials (basal portion) with monocrotophos 36% EC @ 0 15 kgha-1 at 100 DAP + neem cake @ 1.5 tha-1 at 180 DAP + three times manual weeding]. By yield performance and reduction of percentage of wilted plants and mealy bug population, T3 was the best and T2 ranked second. Percent of wilted plants in T1 , T2 and T3 were 11.88, 4.19, 2.62; mean mealy bug population/plant were 9.33, 5.29, 4.20, and yields were 32.5 tha-1, 38.7 tha-1, 41.6 tha-1, respectively. Benefit: Cost ratio was highest in T3 (1.30)
Keywords: Pineapple; Clean cultivation,; Dysmicoccus brevipes; management; planting material treatment; mealybug wilt